Mental Health Diagnoses in Patients With Mycosis Fungoides and Potential Impact on Oncologic Outcomes - Jackson N. Howell; Bayarmaa Mark; David A. Wada; Marianne Bowling; Mei Wei; Shane L. Lloyd; David K. Gaffney; Amit Maity; Michael J. LaRiviere; William G. Rule; Jon D. Grant; Vikrant Deshmukh; et al. (Cancer Medicine)
ABSTRACT Background We investigated mental health diagnoses (MHDs) in mycosis fungoides (MF) patients compared to the general population, evaluated risk factors, and studied survival outcomes in a large population database. Methods MF patients from the Utah Cancer Registry diagnosed from 2001 to 2014 were matched with up to five general population individuals from the Utah Population Database. MHDs were retrospectively tracked in both populations (median follow‐up = 6.67 years). Risk factors for new MHDs among MF patients were studied using the Cox proportional hazards model. Overall survival (OS) and disease‐specific survival (DSS) were assessed using Kaplan–Meier analysis. Results The incidence of anxiety disorders (HR = 1.99, 95% CI [1.16, 3.42]) and delirium/dementia disorders (HR = 2.43, 95% CI [1.05, 5.63]) was higher among MF patients than the matched general population. Among MF patients, Charlson Comorbidity Index (CCI) ≥ 2 and BMI < 18 kg/m2 were risk factors for new anxiety disorders. Radiation therapy, CCI ≥ 2, and female gender were risk factors for new delirium/dementia disorders. The 15‐year OS was worse for MF patients with versus without an MHD (36% vs. 81%, HR 2.62, 95%CI [1.24, 5.65]). The 15‐year DSS also worsened for MF patients with versus without an MHD (63% vs. 97%, HR 6.55, 95%CI [1.64, 26.2]). Conclusions MF patients developed anxiety and delirium/dementia disorders at rates above the general population, and MHDs correlated with worse DSS and OS. Careful mental health monitoring may be an actionable step towards improving health‐related quality of life in this population.